Review Artikel: Metode untuk Meningkatkan Absorpsi Obat Transdermal - Annisa, Viviane (Journal of Islamic Pharmacy, 2020)
The route of administration of transdermal drugs is preferred because it is easy to use. However, there are limitations associated with the difficulty of drugs penetrating into the skin. This is caused by the presence of the stratum corneum which is the main barrier for drug entry into the skin. Penetration of the drug into the skin can be through the trans-epidermal (transcellular and paracellular) route and the trans-appendegeal route depending on the dosage form. To increase the penetration ability of transdermal drugs, it can use chemical enhancers and physical enhancers. Chemical enhancers can be classified based on chemical structure or based on the mechanism of action. Chemical compounds that have the same functional groups can have different mechanisms of action depending on the physical-chemical nature. Chemical enhancers are categorized based on their chemical structure, including: water, alcohol, amides, esters, alcohol ethers, pyrrolidone, hydrocarbons, sulfides, surfactants, terpenes, phospholipids, vesicles. Whereas physical enhancers in the form of drug delivery use external energy to encourage or physically damage the stratum corneum. Physical enhancer methods such as Iontophoresis, Electroporation, Magnetophoresis, Sonophoresis, Photomechanics, Radiofrequency, Thermophoresis, Microneedle, and Jet Injectors.Â Keyword: transdermal; permeation enhancer; chemical enhancer; physical enhancer